THE INFLUENCE OF FINANCIAL LITERACY, HEDONIC LIFESTYLE, AND POCKET MONEY ON PERSONAL FINANCIAL MANAGEMENT BEHAVIOR OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, PADANG STATE UNIVERSITY: Pengaruh Literasi Keuangan, Lifestyle Hedonis, dan Uang Saku Terhadap Perilaku Pengelolaan Keuangan Pribadi Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Padang - Annisa Khariani; Friyatmi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Students from Padang State University's Faculty of Economics and Business will be the subjects of this study, which seeks to answer questions about their own money management habits as a function of financial literacy, hedonic lifestyle, and pocket money. This study used a quantitative methodology based on an associative descriptive approach. Using a proportionate random selection approach, 97 students were chosen as the sample for this study. Multiple regression analysis is the data analysis approach used in this study. A student's personal financial management behavior can be influenced by financial literacy, hedonic lifestyle, pocket money, and all three factors combined. The findings of this study should provide students with the knowledge and skills necessary to effectively manage their own money and steer clear of any financial difficulties in the future